An Ultra-Thin Low-Frequency Tunable Metamaterial Absorber Based on Lumped Element - Zhang, GuoWen; Gao, Jun; Cao, Xiangyu; Yang, HuanHuan; Jidi, Liaori (Společnost pro radioelektronické inženýrství, 2019)
In this paper, an ultra-thin metamaterial absorber with a stretching transformation (ST) pattern is proposed and fabricated in the low-frequency range. The absorber is composed of dielectric layer, metal patch loading resistor and variable capacitor which produce its tunability. In order to expand the tunable bandwidth, we applied the ST with various coefficients x and y to the unit cell pattern. Measurement and simulated results show that the structure can be tuned to provide a continuously variable reflectivity level of less than -10 dB from 0.68 to 2.13 GHz at bias voltages of 10–40 V. The total thickness of this absorber was only λ/31 of the center frequency. Both measurements and simulated results indicate that this absorber can be thin and achieve a tunable absorption simultaneously.
Keywords: low-frequency; wideband; ultra-thin; ST coefficients; tunability.